(untitled) - Smith, Ian (Chichester, West Sussex, 2014)
Smith’s Elements of Soil Mechanics brings additional material on geotechnical design to Eurocode 7 in an understandable format. Many worked examples are included to illustrate the processes for performing design to this European standard. Significant updates throughout the book have been made to reflect other developments in procedures and practices in the construction and site investigation industries. More worked examples and many new figures have been provided throughout. The illustrations have been improved and the new design and layout of the pages give a lift.
Keywords: Chất rắn,Soil mechanics